Análisis comparativo entre pavimento flexible y rígido para uso en ruta cantonal de El Guarco - Hurtado-Acuña, Randy Eduardo (Instituto Tecnológico de Costa Rica, 2016)
The purpose of this project is to select the kind of pavement to be built on a road of Rural Road Network of El Guarco, Cartago. The options to analyze are flexible pavement and rigid pavement. In both cases, pavement design will be considered three alternatives. The first alternative consist of the pavement above the subgrade without stabilization. The second alternative is the pavement above a stabilized subgrade. The third option consists of a pavement over the current structure. Using the AASHTO Guide for Design of Pavement Structures 1993, a structural design is assessed for each pavement alternatives First it is necessary to measure the Average Daily Traffic (ADT) of the route to calculate the Equivalent Single Axle Loads (ESAL), which represents the Vehicle Loads over the pavement structure during the pavement design. After obtaining the pavement geometric and mechanical properties that best supports each alternative, the next step is planning pavement interventions, as well as making a cost analysis. The goal of this is to have all inputs for a comparative analysis with the pavement management system software HDM-4.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2016.
Keywords: Pavimento flexible; Pavimento rígido; Flujo vehicular; Costos; HDM-4